The Construction of the Other: (Re)producing Bare Life - Leban, Sebastjan (AM Journal of Art and Media Studies, 2017)
This paper proposes a critical reading of the formation of the Other within capitalism and coloniality. Through an analysis of the master/slave relation, the master/slave dialectic and bare life/sovereignty, the research intends to prove that the construction of the Other is essential for the construction of Western hegemony. In the first part, we are presented with the construction of the Other within Aristotle’s master/slave relation that is in the second part related to the master/slave dialectic and racial classification. The paper concludes with a critical reflection on Agamben's term homo sacer and gives a short overview of its possible reinvention. The analysis provides an understanding of the construction of the Other in the current state of exception and seems to be crucial in a time where processes of oppression, dispossession and segregation executed upon the Other are increasing.